(untitled) (Delta Medical College Journal, 2018)
Hepatitis C virus (HCV) exists as a cloud of closely related sequence variants called a quasispecies, rather than as a population of identical clones. To date there is no preventive vaccine and though antiviral therapy has been improved in the past few years the HCV cannot be eradicated in all patients as a result of its quasispecies nature due to lack of proof reading activities and high error rate of RNA-dependent RNA polymerase and the pressure exerted by host immune system. This review focuses on the genetic diversity and quasispecies nature of HCV viral genomes, and briefly reviews the principles of quasispecies dynamics and the differences with classical population genetics and discusses the biological implications of this phenomenon, focusing on the hepatitis C virus. Delta Med Col J. Jan 2018 6(1): 45-52